2004
DOI: 10.1093/nar/gkh834
|View full text |Cite
|
Sign up to set email alerts
|

Solving the riddle of codon usage preferences: a test for translational selection

Abstract: Translational selection is responsible for the unequal usage of synonymous codons in protein coding genes in a wide variety of organisms. It is one of the most subtle and pervasive forces of molecular evolution, yet, establishing the underlying causes for its idiosyncratic behaviour across living kingdoms has proven elusive to researchers over the past 20 years. In this study, a statistical model for measuring translational selection in any given genome is developed, and the test is applied to 126 fully sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
705
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 674 publications
(730 citation statements)
references
References 42 publications
24
705
0
1
Order By: Relevance
“…Codon and anticodon usages of each viral population were inferred through the analysis of the sequences of 50 molecular clones of two capsid genomic regions (comprising codons 1 to 123 of VP3 and 85 to 245 of VP1) and compared with codon and anticodon usage of the host cell as previously described (17,33). Anticodon usage variation was estimated through codon usage variation assuming a model based on the frequency of the codons, the anticodon degeneracy, and the codonanticodon match pairing preferences (17,33).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Codon and anticodon usages of each viral population were inferred through the analysis of the sequences of 50 molecular clones of two capsid genomic regions (comprising codons 1 to 123 of VP3 and 85 to 245 of VP1) and compared with codon and anticodon usage of the host cell as previously described (17,33). Anticodon usage variation was estimated through codon usage variation assuming a model based on the frequency of the codons, the anticodon degeneracy, and the codonanticodon match pairing preferences (17,33).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Others have investigated the effects of GC-content on expected bias scores [8], [39], [40], though these analyses did not explore whether measuring deviation from such expected values could enhance prediction of translational efficiency bias. The study by dos Reis et al [39] used a correlation between their transfer RNA adaptation index and deviation from expected effective number of codons to make a determination of whether the underlying bias was that of translational efficiency bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still debated whether tRNA abundance and codon usage are under concerted regulation of translation rate and efficiency. 18-20 In fact, several studies have suggested that preferentially used codons are not translated faster, and that tRNA variation might play an adaptive role in coping with environmental changes. Analysis of human tRNAs using microarrays have revealed that tRNAs could be biasedly induced toward different cell programs such as proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%